Estudo sobre resiliência econômica, moeda e território: abordagem teórica e aplicação empírica para o caso brasileiro - Igor Santos Tupy (2018)
This thesis analyzes, theoretically and empirically, the relations between the monetary system and the economic resilience, under a regional perspective. The study of resilience aims to understand the different ways regional economies deal with recessive shocks in terms of reaction, response, recovery and adaptation. In theoretical terms, this work aims to contribute to the Regional Resilience Theories by the incorporation of an unexplored set of its determinants: the monetary elements. To do this, it proposes to associate elements of the Post-Keynesian Theory about the role of money and banking on the economy and the evolutionary approach to regional resilience. From these two approaches, the thesis argues that the money inserts itself in a complex combination of factors that determines the resilience of regions to recessive shocks, directly and indirectly. Empirically, it was applied Panel Data Methods to investigate how banking variables, mainly credit, impacts the short terms of resilience. Using a logistic regression with fixed effects the determinants of the vulnerability of Brazilian microregions were analyzed. Moreover, the work estimated the impacts of these set of variables on the regional capacity to resist from shocks, since they happened. The empirical analysis focused on the behavior of formal employment in Brazilian microregions during the period 1995-2016. Results have attested the importance of the monetary system to explain the uneven capacity of resilience between Brazilian regions. On the one hand, it was found a direct relation between the credit variable and the vulnerability of regions to downturns in economic activity. On the other hand, results show credit as a key-determinant of the resistance of regions, since they are in crisis. Finally, the thesis proposes to analyze, in an exploratory way, the Brazilian Banks’ strategies to keep themselves resilient over this period. In this sense, the work discusses the adaptation and adaptability of the Banking System to maintain their high profits, focusing at the market concentration and at the increasing use of financial innovations. We argue, then, that this behavior contributes to keep the banking system dysfunctionality to regional development in Brazil.